Surface-enhanced Carboxyphenyl diazonium functionalized screen-printed carbon electrode for the screening of tuberculosis in sputum samples - Yunus, Muhammad Hafiznur; Yusof, Nor Azah; Ismail, Suhainie; Md Noor, Siti Suraiya; Mohammad, Faruq; Sulaiman, Yusran; Ahmad Raston, Nurul Hanun; Abdullah, Jaafar; Soleiman, Ahmed A. (Multidisciplinary Digital Publishing Institute, 2022)
Curbing tuberculosis (TB) requires a combination of good strategies, including a proper prevention measure, diagnosis, and treatment. This study proposes an improvised tuberculosis diagnosis based on an amperometry approach for the sensitive detection of MPT64 antigen in clinical samples. An MPT64 aptamer specific to the target antigen was covalently attached to the carboxyphenyl diazonium-functionalized carbon electrode via carbodiimide chemistry. The electrochemical detection assay was adapted from a sandwich assay format to trap the antigen between the immobilized aptamer and horseradish peroxidase (HRP) tagged polyclonal anti-MPT64 antibody. The amperometric current was measured from the catalytic reaction response between HRP, hydrogen peroxide, and hydroquinone, which is used as an electron mediator. From the analysis, the detection limit in the measurement buffer was 1.11 ng mL-1. Additionally, the developed aptasensor exhibited a linear relationship between the current signal and the MPT64 antigen-spiked serum concentration ranging from 10 to 150 ng mL-1 with a 1.38 ng mL-1 detection limit. Finally, an evaluation using the clinical sputum samples from both TB (+) and TB (-) individuals revealed a sensitivity and specificity of 88% and 100%, respectively. Based on the analysis, the developed aptasensor was found to be simple in its fabrication, sensitive, and allowed for the efficient detection and diagnosis of TB in sputum samples.